Curing enhancement and network effects in multi‐walled carbon nanotube‐filled vulcanized natural rubber: evidence for solvent sensing. Issue 6 (17th March 2017) - Ponnamma, Deepalekshmi; Varughese, Konnanilkunnathil Thomas; Al‐Maadeed, Mariam Al Ali; Thomas, Sabu
Abstract: Electrically and thermally conductive polymer composites offer great possibilities in various electronic fields because of their low weight and ease of processing. This paper addresses the curing behaviour and network properties of conducting multi‐walled carbon nanotube (MWCNT)‐reinforced natural rubber (NR) nanocomposites, emphasizing the sensing and diffusion performances. NR/MWCNT composites were prepared following a special master batch technique which allows the appropriate distribution of nanotubes within the elastomer. The sensing responses of the composites towards solvents were observed as variations in electrical resistance. Thermal resistance and glass transition behaviour were examined and correlated with the swelling measurements as evidence for solvent sensing. An optimum level of 3 phr of MWCNTs is understood to lead to the best properties for the NR/MWCNT composites. Finally, the structural morphology and interfacial interactions were found to have correlations with cure reactions, glass transition temperatures and sensing responses of all compositions. © 2017 Society of Chemical Industry Abstract : Multi‐walled carbon nanotubes form a three‐dimensional conducting network within natural rubber. This causes solvent sensing and this is substantiated from curing and swelling studies.